Differential Expression of EGFR-1, MMP-3, and MMP-9 in Spontaneous Abortions, Induced Abortions, and Tubal Pregnancies - Mahi BALCI; Gülhan ÖZDEMIR (Federation of Turkish Pathology Societies, 2019)
Objective: The purpose of our study was to assess trophoblastic and uterine sufficiency in miscarriage pathogenesis with immunohistochemical methods and to determine if they could be used as a screening tool for the risk of miscarriage in the future. Material and Method: Placental tissue specimens that were comprised of 20 spontaneous abortions, 23 voluntarily terminated (induced) abortions, and 12 tubal pregnancies were included in this study. Trophoblastic cells and implantation area were evaluated for staining with EGFR-1, MMP-3, and MMP-9 by immunohistochemistry. Results: EGFR-1 expression was more intense and diffuse in decidual cells in the placental bed of spontaneous abortion specimens; this difference was statistically significant (P=0.004). MMP-3 expression was markedly increased in villous and extravillous trophoblastic cells in induced abortions; the difference between the groups was found to be statistically significant (P values ranged from < 0.01 to 0.005). MMP-9 expression tended to be higher in spontaneous abortion and tubal pregnancy specimens, and the results were statistically significant as P values were lower than 0.01. Conclusion: Higher EGFR-1 expression in the decidual tissue of spontaneous abortion specimens suggests that EGFR-1 triggers the migration of extravillous trophoblasts, leading to their destructive invasion. Similarly, MMP-9 immunopositivity might be indicative of aggressive invasion contributing to spontaneous abortion pathogenesis. Relatively high levels of MMP-3 expression in induced abortion specimens used as a control group might be a predictor of successful implantation, whereas its decreased expression might be indicative of risk for pregnancy loss.